Práticas de produção textual e a formação continuada de professores: percursos em diálogo - Adriano, Maria José (2021)
The present work chooses as a theme the production of text articulated to the formation of teachers and seeks to answer the following question: how is the textual production worked in classes of the third year of elementary school I? The general objective that guided this research was to contribute to the process of continuing teacher education through the production of pedagogical support material for the work with the production of texts in the classroom, in classes of the third year of Elementary School. As specific objectives, the following are listed: (i) understand about the teacher training process through continuing education courses (ii) analyze the strategies used by teachers of the third year of elementary school to plan and propose activities for the production of classroom text. A theoretical research was carried out on the theme, from some authors such as: Gatti (1997), Tardif (2002), Geraldi (2001) and Dolz (2010). The methodological approach is in line with a qualitative research and the data collection occurred through interviews with teachers on the topic of textual production. Data analysis showed that teachers use different strategies to work with textual production in the classroom and consider that continuing education courses contribute to pedagogical practice. Complementary material was prepared with proposals for textual production aimed at working with 3rd year students of the initial years.